PENGARUH INTERNET FINANCIAL REPORTING DAN TINGKAT PENGUNGKAPAN INFORMASI WEBSITE TERHADAP FREKUENSI PERDAGANGAN SAHAM PERUSAHAAN - dul muid; febrian hargyantoro (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2012)
Because of rapidly growth of internet technology, communication through internet has been adopted by business sector as important tool to share information. Growth of information technology especially internet influenced traditional form of company information disclosure until additional media to disclose financial information that which is Internet Financial Reporting (IFR) has emerged. Then, there are efforts of companies to reduce asymmetry information by disclose information about companies. This research has objective to know the influence of IFR practice and degree of information disclosure on website to frequency of trading stock of company.This research use cross sectional data. The amount of sample is 100 company on Kompas100 index until end of 2009. Linear Regression is used to find out the impact of IFR practice and degree information of website to trading stock frequency of company. This research show that there is impact of IFR practice and degree of information disclosure on website to trading stock frequency of company.